GEOMORPHOLOGICAL COMPOSITION OF NUMBER AREAS OF ALPINE LAKES IN ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The results of field studies of the relief and relief-forming processes in the basins of four alpine lakes of Armenia (Kari, Umroy, Akna, and Sev) are presented. It has been established that the catchment basins of all these lakes are characterized by generally similar relief and approximately the same exogenous relief-forming processes. Some difference is typical for the Lake Sev basin due to its slightly lower absolute heights. From the exogenous processes of relief formation in the Lake Kari basin can be noted as a weak solifluction in the form of sod creeping onto boulders on the surface of the watershed plateau and nivation at the sites of snowbanks formation. Solifluction is most clearly manifested on the slopes of the cinder cones in the Lake Akna basin, which is related to the nature of the rocks composing these cones. Here, nivation easily forms niches of the same name in places where snowbanks form. For the Lake Sev basin the processes of congelifluction (displacement of chingils) on the slopes of lava flows are of predominant importance. The nature of the moraine relief of the Lake Umroy basin is a good indicator of identifying the stages of retreat of the Würm glacier.
Keywords: drainage basin; congelifluction; nivation; relief; solifluction